Assessment of transmission length of prestressing strands according to fib Model Code 2010. (15th September 2017) - Dang, Canh N.; Hale, W. Micah; Martí-Vargas, J.R.
Highlights: High-strength concrete was used to cast pretensioned concrete beams. Transmission length and strand draw-in of 18-mm prestressing strands were measured. The fib Model Code 2010 is conservative in predicting the transmission lengths. The use of high-strength concrete can shorten the transmission length. A center-to-center strand spacing of 50 mm is applicable for high-strength concrete. Abstract: The use of 18-mm prestressing strands is advantageous in the construction of long-span bridges. Transmission length is a significant parameter in the design of pretensioned concrete members. This study provides a unique set of experimental data to validate the applicability of using the fib Model Code 2010 to predict the transmission length and strand draw-in of 18-mm strands. Twelve pretensioned concrete beams were cast with high-strength concrete. Transmission lengths were measured at prestress transfer and at 28-day of age. The experimental results indicated the lower and upper bounds of transmission length specified by the code adequately predict the measured values.